Reading habit among Bachelor in Information Studies (BIS) students / Aina Natasha Azizan - Azizan, Aina Natasha (Faculty of Information Management, 2010)
Reading habit is a complex cognitive process of decoding symbols for the intention of deriving meaning and constructing meaning. It is comprising a range of other skills, including those that allow to decide from context what is intended by words that can have more than one meaning, and to seize from a look at a large piece of print the general meaning intended, without reading each individual word. This study seeks to identify the reading habit among BIS students in UiTM Kedah. However, reading habit is very poor in application to reading. The study tends to determine the relationship between reading habit among BIS students with the reading material, format of information and environment of t reading among students.